2003
DOI: 10.1074/jbc.m209964200
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Antiviral Activity of Recombinant Natural Killer Cell Enhancing Factors, NKEF-A and NKEF-B, Members of the Peroxiredoxin Family

Abstract: CD8؉ T-cells are a major source for the production of non-cytolytic factors that inhibit HIV-1 replication. In order to characterize further these factors, we analyzed gene expression profiles of activated CD8؉ T-cells using a human cDNA expression array containing 588 human cDNAs. mRNA for the chemokine I-309 (CCL1), the cytokines granulocyte-macrophage colony-stimulating factor and interleukin-13, and natural killer cell enhancing factors (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 60 publications
2
72
0
Order By: Relevance
“…Moreover, results from RT-PCR analysis conducted on purified CD4 ϩ and CD8 ϩ T cells from each cohort confirmed that PRDX2 was mainly expressed in CD8 ϩ T cell subset and that the expression of IL-22 transcripts was exclusively observed in the CD4 ϩ T cell subset (results not shown). These results are in line with the literature data reporting that IL-22 is produced by activated CD4 ϩ CD45RO ϩ T lymphocyte subset and, to a certain extent, NK cells (23) and that PRDX2 is mainly produced by CD8 (21). In PBMC, as expected, the CD4-CD8 ratio from all HIV ϩ was inversed, as compared with that from the HC and EU (Tables I and II), whereas the population of memory CD4 ϩ /CD45RO ϩ T cells from EU was proportionally increased (data not shown), as had already been demonstrated before for this particular cohort of individuals (13).…”
Section: Activated T Cells From Eu Overexpress Transcripts Of Il-22 Asupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, results from RT-PCR analysis conducted on purified CD4 ϩ and CD8 ϩ T cells from each cohort confirmed that PRDX2 was mainly expressed in CD8 ϩ T cell subset and that the expression of IL-22 transcripts was exclusively observed in the CD4 ϩ T cell subset (results not shown). These results are in line with the literature data reporting that IL-22 is produced by activated CD4 ϩ CD45RO ϩ T lymphocyte subset and, to a certain extent, NK cells (23) and that PRDX2 is mainly produced by CD8 (21). In PBMC, as expected, the CD4-CD8 ratio from all HIV ϩ was inversed, as compared with that from the HC and EU (Tables I and II), whereas the population of memory CD4 ϩ /CD45RO ϩ T cells from EU was proportionally increased (data not shown), as had already been demonstrated before for this particular cohort of individuals (13).…”
Section: Activated T Cells From Eu Overexpress Transcripts Of Il-22 Asupporting
confidence: 93%
“…The presence of PRDX2 has been reported in long-term nonprogressors, where it exhibits a strong, direct anti-HIV-1 activity in vitro (21). In contrast, IL-22 acts as an innate immune inducer; and because of its target cells, the only possible anti-HIV-1 activity of this cytokine is indirectly exerted by its downstream acute phase products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Prdx2 has been reported to be important for the maintenance of anti-viral activity in CD8 þ T cells. 41 The knockout of Prdx2 in mice has been shown to cause an increase in T cells and dendritic cells 42 and increases in Figure 5 Silencing of one gene (Bcl2) in CD8 þ T cells from tolerized mice does not effect expression of other selected genes known to be involved (or not) in suppressive capacity of CD8 þ Treg in our system. CD8 þ T cells were isolated from pCons-treated mice 1 week after pCons tolerization using antibody-specific microbeads from AUTOMACS.…”
Section: Discussionmentioning
confidence: 83%
“…NKEF-A and -B, later identified as PrxI and PrxII respectively [6], can be detected in a wide range of tissues [7,8]. The NKEF protein may be also involved in apoptosis [9,10], cell proliferation, differentiation [11,12] and anti-viral activity in vitro [13]. Although recombinant NKEF (rNKEF)-A and -B have similar levels of antioxidant function, only the reduced form of rNKEF-A can enhance NK cytotoxicity, which indicates that both the antioxidant and NK-enhancing functions of rNKEF-A and -B probably involve the cysteine residues of the proteins but are mediated by separate domains of the molecules [14].…”
Section: Introductionmentioning
confidence: 99%